An improved wear resistance of stirring tool for reconfigured friction stir welding (FSW) machine / Normariah Che Maideen ... [et al.] - Che Maideen, Normariah; Budin, Salina; Mohd Shah, Aziurah; Hyie, Koay Mei; Zulkifli, Mohamad Zulkarnain (2020)
Friction Stir Welding (FSW) is a solid-state welding process that is capable to weld high variety of material and able to joint similar or dissimilar material. Currently, there are dedicated FSW machine available in the market. However, for commercial use, the machine is expensive. Therefore, there is a technique, using reconfigured milling machine to performed FSW process. However, there is a need for special arrangement for this reconfigured milling machine to perform FSW such as customized jig and fixture and stirring tool. In this work, an improved wear resistance of stirring tool has been innovated. Four stirring tools has been design, fabricated, and tested. Aluminum AA6061-T6 with dimension of 120 x 50 x 5 mm have been used as the specimen to perform the welding process by using 1270 rpm of rotating speed and 218 mm/min of welding speed. The best wear resistance of stirring tool is tool that has been heat treated and coated with TiCN (Tool no. 4). The physical appearance of stirring tool after performed FSW process shows a significant improvement by capturing no physical wear. The wear rate is minimum which is 0.3% compared before improvement which is 6%. Therefore, the innovated stirring tool has improved 95%.